Assessing Hearing Conservation Program Effectiveness: Results of a Multisite Assessment. Issue 1 (January 2018) - Rabinowitz, Peter; Cantley, Linda F.; Galusha, Deron; Trufan, Sally; Swersey, Arthur; Dixon-Ernst, Christine; Ramirez, Vickie; Neitzel, Richard
Abstract : Objectives: Noise-induced hearing loss (NIHL) remains one of the most prevalent occupational diseases. Occupational hearing conservation programs (HCPs) can reduce the risk of NIHL, but there remains no consensus on assessing HCP effectiveness. We conducted a multisite, mixed-method assessment of HCP programs. Methods: At 13 manufacturing plants, we performed assessments, including interviews with program staff and worker focus groups and surveys. We analyzed the association between these assessments and age-corrected NIHL rates. Results: Only a few items from the HCP staff interviews correlated with NIHL rates. For the employee survey, management commitment to NIHL prevention and being counseled about NIHL were strongly associated with NIHL rates. Conclusion: Management commitment and counseling of workers about NIHL may be key factors in program effectiveness. A combination of qualitative and quantitative methods appears to be useful for assessing HCPs. Abstract : Supplemental Digital Content is available in the text